Deficiencies of the lipid-signaling enzymes phospholipase D1 and D2 alter cytoskeletal organization, macrophage phagocytosis, and cytokine-stimulated neutrophil recruitment. - Wahida H Ali; Qin Chen; Kathleen E Delgiorno; Wenjuan Su; Jason C Hall; Tsunaki Hongu; Huasong Tian; Yasunori Kanaho; Gilbert Di Paolo; Howard C Crawford; Michael A Frohman (PLoS ONE, 2013)
Cell migration and phagocytosis ensue from extracellular-initiated signaling cascades that orchestrate dynamic reorganization of the actin cytoskeleton. The reorganization is mediated by effector proteins recruited to the site of activity by locally-generated lipid second messengers. Phosphatidic acid (PA), a membrane phospholipid generated by multiple enzyme families including Phospholipase D (PLD), has been proposed to function in this role. Here, we show that macrophages prepared from mice lacking either of the classical PLD isoforms PLD1 or PLD2, or wild-type macrophages whose PLD activity has been pharmacologically inhibited, display isoform-specific actin cytoskeleton abnormalities that likely underlie decreases observed in phagocytic capacity. Unexpectedly, PA continued to be detected on the phagosome in the absence of either isoform and even when all PLD activity was eliminated. However, a disorganized phagocytic cup was observed as visualized by imaging PA, F-actin, Rac1, an organizer of the F-actin network, and DOCK2, a Rac1 activator, suggesting that PLD-mediated PA production during phagocytosis is specifically critical for the integrity of the process. The abnormal F-actin reorganization additionally impacted neutrophil migration and extravasation from the vasculature into interstitial tissues. Although both PLD1 and PLD2 were important in these processes, we also observed isoform-specific functions. PLD1-driven processes in particular were observed to be critical in transmigration of macrophages exiting the vasculature during immune responses such as those seen in acute pancreatitis or irritant-induced skin vascularization.